An efficient in vitro organogenesis protocol for the endangered relic tree species Bretschneidera sinensis and genetic fidelity assessment using DNA markers - Yan, Xuetong; Zheng, Keyuan; Li, Peng; Zhong, Xin; Zhu, Zongwei; Zhou, Huijing; Zhu, Mulan (Frontiers in Plant Science, 2024)
Bretschneidera sinensis is a monotypic species of rare and tertiary relic trees mainly distributed in China. The B. sinensis is a potentially valuable horticultural plant, which has significant ornamental and research value, and is a crucial tool for the study of phylogeography. The artificial cultivation of B.sinensis is of great scientific value and practical significance. In this study, we developed a direct organogenesis process of B. sinensis using mature zygotic embryos as initial materials. The highest sterile germination induction (54.5 %) from the mature zygotic embryo was obtained in a Murashige and Skoog (MS) medium with 2.0 mg•L -1 6-Benzylaminopurine (6-BA) and 0.2 mg•L -1 α-Naphthaleneacetic acid (NAA). The highest percentage of shoot regeneration (90.37 %) was attained using 1.0 mg•L -1 6-BA and 0.01 mg•L -1 NAA in the MS medium. The Woody Plant Medium (WPM) had the greatest adventitious shoot elongation rate of 93.33 %. The most optimized rooting rate was 88.89 % in a half-strength MS medium containing 2.0 mg•L -1 Indole-3-butyric acid (IBA) and 1.0 mg•L -1 NAA. The genetic fidelity of in vitro regenerated plantlets was assessed using inter-simple sequence repeats and random amplified polymorphic DNA molecular markers, confirming the genetic uniformity and stability of regenerated B. sinensis plantlets. Our research presents an effective in vitro propagation system for B. sinensis, laying the groundwork for its germplasm conservation and large-scale production while maintaining high genetic integrity.